The power of metaphor in medical education: fostering shared understanding in complex conversations - Johnston, Aaron; Andrawis, Sandra; Perez, Grace; Ram, Veronique; Ogbeide, Samuel (Frontiers in Medicine, 2025)
Effective communication in medical education, particularly around complex or emotionally charged topics, remains a significant challenge. While numerous feedback frameworks exist, less attention has been paid to optimizing fundamental linguistic tools like metaphor. Contemporary theory posits metaphor not merely as linguistic ornamentation, but as a conceptual tool that can deepen and even create understanding. This article employs a conceptual review format, drawing on established principles from cognitive psychology, narrative medicine, and adult learning theory. It utilizes illustrative vignettes to present practical applications of metaphor in clinical training environments. We identify, and explore, three key areas where metaphor can be a powerful tool for medical educators: (i) Teaching clinical reasoning, (ii) Opening difficult conversations, (iii) Facilitating discussions on professional identity formation. We identify challenges with metaphor use, such as male gender coded metaphor, and explore areas of caution for the use of metaphor in medical education, including intercultural communication and communication with neurodiverse individuals. We use a strategy called SAFE (Slow down, Acknowledge and Apologize, Follow-up, Explain), as a simple mnemonic for educators to recognize and respond when a metaphor misses the mark. Metaphor is experiencing a renaissance in medical education as a vital tool for fostering shared understanding. Its intentional use can enhance teaching in complex domains like clinical reasoning, difficult conversations, and professional identity. Educators are encouraged to adopt this tool mindfully, with awareness of its potential pitfalls, and a readiness to employ the SAFE strategy when a miss is perceived.